2012
DOI: 10.1016/j.jmb.2011.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Smooth Muscle Heavy Meromyosin Shows an Open Conformation Linked to Activation

Abstract: Smooth muscle myosin and heavy meromyosin (smHMM) are activated by regulatory light chain (RLC) phosphorylation but the mechanism remains unclear. Dephosphorylated, inactive smHMM assumes a closed conformation with asymmetric intramolecular head-head interactions between motor domains. The “free head” can bind to actin, but the actin-binding interface of the “blocked head” is involved in interactions with the free head. We report here a 3-D structure for phosphorylated, active smHMM obtained using electron cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
(101 reference statements)
1
26
0
Order By: Relevance
“…This dual phosphorylation mechanism could be extended to other chelicerate striated muscles, like that of Limulus 6 and scorpion, 7 and possibly other arthropods with thick filaments that exhibit 4-stranded helical tracks of IHMs together with myosin RLCs with a long NTE and two phosphorylatable serines. In contrast, a different activation mechanism is present in vertebrate skeletal 28, 29 and cardiac muscle, 30, 31 which have thick filaments that exhibit a perturbed 3-fold helical array of IHMs, as well as in vertebrate smooth muscle, 32 which also has IHMs but with a proposed ELC activation role, 33 and mollusks, which have 7-fold helical tracks of IHMs with ELC direct Ca 2+ -binding activation control. Below we discuss how the intra- and intermolecular interactions associated with the tarantula model (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dual phosphorylation mechanism could be extended to other chelicerate striated muscles, like that of Limulus 6 and scorpion, 7 and possibly other arthropods with thick filaments that exhibit 4-stranded helical tracks of IHMs together with myosin RLCs with a long NTE and two phosphorylatable serines. In contrast, a different activation mechanism is present in vertebrate skeletal 28, 29 and cardiac muscle, 30, 31 which have thick filaments that exhibit a perturbed 3-fold helical array of IHMs, as well as in vertebrate smooth muscle, 32 which also has IHMs but with a proposed ELC activation role, 33 and mollusks, which have 7-fold helical tracks of IHMs with ELC direct Ca 2+ -binding activation control. Below we discuss how the intra- and intermolecular interactions associated with the tarantula model (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…26, 27 The IHM model has also improved knowledge of the activation mechanism in vertebrate skeletal 28, 29 and cardiac muscle. 30, 31 On the other hand, the smooth muscle IHM (PDB 1I84) structure has improved knowledge of its activation mechanism, 32 including a possible role of myosin ELC. 33 …”
Section: Introductionmentioning
confidence: 99%
“…Although the heads in relaxed filaments presumably have similar intramolecular interactions to those in molecules (9), this has not yet been demonstrated, owing to the lability of these filaments, and potential intermolecular interactions remain unknown. The close relationship between vertebrate smooth and scallop striated muscle myosin (6,18,25,28,48), together with certain structural similarities between scallop and smooth muscle filaments, suggests that the scallop reconstruction may hold clues to molecular organization in the side-polar structure. The packing of myosin heads within a crown in the scallop is much tighter than in other striated muscle filaments (13,15,16), leading to azimuthal contacts between neighboring blocked and free motor domains that are absent from these other systems (Fig.…”
Section: +mentioning
confidence: 99%
“…These contacts suggest possible paths for intramolecular communication that are absent in phosphorylation-regulated structures. However, the RLC domains of the tarantula model (13) were based on a skeletal model (9), and it has since been reported that a scallop model produces a better connection to S2 in this region for smooth muscle (28). Therefore, it is possible that the use of a scallop model may also introduce changes in the tarantula fit.…”
mentioning
confidence: 99%
“…LC 20 phosphorylation is facilitated by the proximity of kinase and substrate: MLCK, an elongated molecule, is anchored via three N-terminal actin-binding sites (with the sequence DFRxxL), and the active site, which is located near the Cterminus, interacts with and phosphorylates Ser19 of LC 20 , located in the neck region of the myosin motor (Stull et al 1998;Mabuchi et al 2010;Hong et al 2011;Sutherland and Walsh 2012). LC 20 phosphorylation abolishes asymmetric intramolecular interactions between the two myosin heads, thereby relieving inhibition of the MgATPase activity and enabling myosin cross-bridge interaction with actin and relative sliding of actin and myosin filaments driven by the energy derived from the hydrolysis of ATP (Wu et al 1999;Wendt et al 2001;Baumann et al 2012;Taylor et al 2014). At the level of the muscle strip, this is reflected by an increase in isometric force (as seen in Fig.…”
Section: Depolarization-induced Contraction Of Vascular Smooth Musclementioning
confidence: 99%